Finite element analysis of the dynamic response of rubberized geopolymer concrete column subjected to lateral impact using ABAQUS - Azunna, Sunday U.; Aziz, Farah N.A.A.; Rashid, Raizal S.M.; Bakar, Nabilah B.A.; Mabood, Tufail (Elsevier Ltd, 2026)
Experimentalverification for lateral impact testing of structural components is quite costly and difficult, which has pushed scientists and researchers to use simulation methods or tools for testing and simulations. This work proposes a Finite Element Method (FEM) approach using ABAQUS for simulating the dynamics of rubberized geopolymer concrete (RuGPC) columns with 0%, 10%, and 20% crumb rubber (CR) substituted for the normal fine aggregate, to measure the influence of stress, damage, displacement, and energy absorption. Parametric CAD models were produced algorithmically with Grasshopper and then exported to ABAQUS software. A concrete damaged plasticity constitutive law with homogenization was adopted for RuGPC, and uniaxial stress-strain relationships as well as damage properties were determined separately using experiments for each CR content. Reinforcement was treated as embedded trusses with perfect binding, and dynamic simulations of impact with the pendulum under preload were performed using surface-to-surface contact. Models were accurate for peak impact force predictions, peak displacements, and identification of damage modes. But impact time and energy absorption were underpredicted for higher CR contents because of the lower viscoelastic damping offered by CDP. The addition of CR contributed to the higher energy-damping capability and ductility of experimental specimens. The FEM framework reasonably captured RuGPC impact behavior, validating enhanced energy absorption for impact-resistant applications while identifying needs for advanced viscoelastic modeling.